2007
DOI: 10.1073/pnas.0611393104
|View full text |Cite
|
Sign up to set email alerts
|

Intergenic variants of HBS1L-MYB are responsible for a major quantitative trait locus on chromosome 6q23 influencing fetal hemoglobin levels in adults

Abstract: Individual variation in fetal hemoglobin (HbF, ␣2␥2) response underlies the remarkable diversity in phenotypic severity of sickle cell disease and ␤ thalassemia. HbF levels and HbF-associated quantitative traits (e.g., F cell levels) are highly heritable. We have previously mapped a major quantitative trait locus (QTL) controlling F cell levels in an extended Asian-Indian kindred with ␤ thalassemia to a 1.5-Mb interval on chromosome 6q23, but the causative gene(s) are not known. The QTL encompasses several gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
286
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(299 citation statements)
references
References 30 publications
5
286
3
5
Order By: Relevance
“…However, DEPDC2 and HBS1L, located on chromosome 8 and chromosome 6, respectively, are in the proximity of the previously reported QTL region that associates with the fetal hemoglobin level. [32][33][34] Thus, the results produced from pHCR analysis are consistent with the known biological factors for this disease, reaffirming the interplay of these two regions.…”
Section: Real Data Setsupporting
confidence: 70%
“…However, DEPDC2 and HBS1L, located on chromosome 8 and chromosome 6, respectively, are in the proximity of the previously reported QTL region that associates with the fetal hemoglobin level. [32][33][34] Thus, the results produced from pHCR analysis are consistent with the known biological factors for this disease, reaffirming the interplay of these two regions.…”
Section: Real Data Setsupporting
confidence: 70%
“…In a subsequent high-resolution association study, the same authors identified multiple genetic variants within and 5′ to HBS1L at 6q23 that are strongly associated with F-cell levels in families of Northern European ancestry [35]. Studies on erythroid progenitors in vitro have clearly shown that only HBS1L expression correlates with high F-cell alleles [36]. It is of interest to note that the HBS1L-MYB intergenic region on chromosome 6q23.3 influences not only F-cell frequency but also a series of hematological parameters, including erythrocyte, platelet, and monocyte counts in humans [37].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 97%
“…Thein (King's College, Londres, Royaume-Uni). Sa mise en évidence remonte à 2007 ; les auteurs avaient alors défini plusieurs segments dans cet intervalle, la liaison la plus forte étant localisée dans une séquence de 24 kb, située à peu près à égale distance de l'un et l'autre des deux gènes [6]. Ces gènes sont tous deux exprimés dans les précurseurs érythroïde.…”
Section: Perspectives Thérapeutiquesunclassified